LITERATURE IN THE XXI CENTURY CLASSROOM: TEACHING STRATEGIES AND STUDENT ENGAGEMENT - Kuldasheva, Malika (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This article describes contemporary approaches to teaching literature in the XXI century classroom with particular emphasis on strategies that strengthen student engagement. In modern education, literature is no longer taught only as a body of canonical texts to be interpreted through teacher-centered explanation; it is increasingly viewed as a dynamic pedagogical space for developing critical thinking, empathy, creativity, communication, and cultural awareness. The study explores how interactive instruction, digital technologies, learner-centered pedagogy, project-based learning, collaborative interpretation, and differentiated teaching can transform the literature classroom into an active environment of meaning-making. Special attention is given to the role of text selection, classroom dialogue, multimodal tasks, and reflective response in sustaining students’ motivation and participation. Additionally, the article highlights the possibilities of enhancing students’ independent thinking skills, encouraging their active participation, and improving lesson effectiveness through the implementation of modern pedagogical technologies in practice. It is emphasized that the use of innovative approaches in the educational process can increase students’ motivation and help address their individual needs and interests. The research findings indicate that the application of modern strategies in literature classes not only deepens knowledge but also develops students’ analytical and creative thinking skills. At the same time, these approaches ensure effective communication between teachers and students, making the learning process more meaningful and interactive. The results of this study have significant theoretical and practical importance for improving the methodology of teaching literature in the 21st-century education system.